GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Letter to the Editor regarding Chappell et al., 2023, “Satellites reveal Earth's seasonally shifting dust emission sources” - Natalie Mahowald; Paul Ginoux; Gregory S. Okin; Jasper Kok; Samuel Albani; Yves Balkanski; Mian Chin; Gilles Bergametti; Thomas F. Eck; Carlos Pérez García-Pando; Antonis Gkikas; María Gonçalves Ageitos; et al. (Science of The Total Environment, 2024)

Repeated seismic swarms near Paricutin volcano: precursors to the birth of a new monogenetic volcano in the Michoacán-Guanajuato volcanic field, México? - D. Legrand; M. Perton; J. L. Macías; C. Siebe; J. Pacheco; F. Chacón; J. Lermo; L. Quintanar; G. Cisneros (Bulletin of Volcanology, 2023)
The birth of a new monogenetic volcano is difficult to forecast with precision, both in space and time. Nevertheless, seismic activity can alert of the imminence of such an eruption because it usually occurs as small-magnitude earthquake swarms that can last for a few weeks to months prior to an eruption. These swarms are usually related to magma that becomes stalled in the Earth’s crust for variable periods of time before its eventual eruption at the surface. For several reasons, volcanic seismic swarms have rarely been recorded with seismometers before the birth of a new monogenetic volcano. Over the past 25 years, six distinct seismic swarms (in 1997, 1999, 2000, 2006, 2020, and 2021) were detected between Tancítaro and Paricutin volcanoes, in the southwestern part of México’s Michoacán-Guanajuato volcanic field. They are believed to represent repeated attempts of magma to reach the surface hinting that in this region magma might become stalled for some time, so as to not reach the surface in a single ascent event from its source in the mantle. To better understand the magma’s migration path through the crust, we re-located with greater precision some of these seismic swarms by using the same methodology and velocity model to the entire data set. Our results show that these swarms originated within a small area beneath the NE flank of Tancítaro at depths of between 15 and 8 km below sea level (bsl). Apparently, magma is trying to reach the surface within the same conduit network at these crustal depths, but stalls when reaching a depth of ~ 8 km bsl. It is crucial to study these swarms because they might be precursors to a new eruption in this part of the Michoacán-Guanajuato volcanic field. This monogenetic field has been very active, producing several dozen eruptions during the Holocene, the last two Jorullo (1759–1774) and Paricutin (1943–1952). Furthermore, the Tancítaro area displays one of the highest densities of Holocene volcanoes within the entire field, making it a probable candidate location for the birth of a future monogenetic volcano. For these reasons, a permanent seismic network should be installed as soon as possible.

Plant phenology drives seasonal changes in shear stress partitioning in a semi-arid rangeland - Nancy P. Ziegler; Nicholas P. Webb; John A. Gillies; Brandon L. Edwards; George Nikolich; Justin W. Van Zee; Brad F. Cooper; Dawn M. Browning; Ericha M. Courtright; Sandra L. LeGrand (Agricultural and Forest Meteorology, 2023)

Regional integration of long-term national dense GNSS network solutions - Ambrus Kenyeres; J. G. Bellet; C. Bruyninx; A. Caporali; F. de Doncker; B. Droscak; A. Duret; P. Franke; I. Georgiev; R. Bingley; L. Huisman; L. Jivall; et al. (GPS Solutions, 2019)
The EUREF Permanent Network Densification is a collaborative effort of 26 European GNSS analysis centers providing series of daily or weekly station position estimates of dense national and regional GNSS networks, in order to combine them into one homogenized set of station positions and velocities. During the combination, the station meta-data, including station names, DOMES numbers, and position offset definitions were carefully homogenized, position outliers were efficiently eliminated, and the results were cross-checked for any remaining inconsistencies. The results cover the period from March 1999 to January 2017 (GPS week 1000-1933) and include 31 networks with positions and velocities for 3192 stations, well covering Europe. The positions and velocities are expressed in ITRF2014 and ETRF2014 reference frames based on the Minimum Constraint approach using a selected set of ITRF2014 reference stations. The position alignment with the ITRF2014 is at the level of 1.5, 1.2, and 3.2 mm RMS for the East, North, Up components, respectively, while the velocity RMS values are 0.17, 0.14, and 0.38 mm/year for the East, North, and Up components, respectively. The high quality of the combined solution is also reflected by the 1.1, 1.1, and 3.5 mm weighted RMS values for the East, North, and Up components, respectively.

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Effects of in situ CO2 enrichment on Posidonia oceanica epiphytic community composition and mineralogy - T. E. Cox; M. Nash; F. Gazeau; M. Déniel; E. Legrand; S. Alliouane; P. Mahacek; A. Le Fur; J.-P. Gattuso; S. Martin (Marine Biology, 2017)

Metapopulation theory identifies biogeographical patterns among core and satellite marine bacteria scaling from tens to thousands of kilometers - Markus V. Lindh; Johanna Sjöstedt; Börje Ekstam; Michele Casini; Daniel Lundin; Luisa W. Hugerth; Yue O. O. Hu; Anders F. Andersson; Agneta Andersson; Catherine Legrand; Jarone Pinhassi (Environmental Microbiology, 2017)
Summary Metapopulation theory developed in terrestrial ecology provides applicable frameworks for interpreting the role of local and regional processes in shaping species distribution patterns. Yet, empirical testing of metapopulation models on microbial communities is essentially lacking. We determined regional bacterioplankton dynamics from monthly transect sampling in the Baltic Sea Proper using 16S rRNA gene sequencing. A strong positive trend was found between local relative abundance and occupancy of populations. Notably, the occupancy‐frequency distributions were significantly bimodal with a satellite mode of rare endemic populations and a core mode of abundant cosmopolitan populations (e.g. Synechococcus , SAR11 and SAR86 clade members). Temporal changes in population distributions supported several theoretical frameworks. Still, bimodality was found among bacterioplankton communities across the entire Baltic Sea, and was also frequent in globally distributed datasets. Datasets spanning waters with widely different physicochemical characteristics or environmental gradients typically lacked significant bimodal patterns. When such datasets were divided into subsets with coherent environmental conditions, bimodal patterns emerged, highlighting the importance of positive feedbacks between local abundance and occupancy within specific biomes. Thus, metapopulation theory applied to microbial biogeography can provide novel insights into the mechanisms governing shifts in biodiversity resulting from natural or anthropogenically induced changes in the environment.

Disentangling seasonal bacterioplankton population dynamics by high‐frequency sampling - Markus V. Lindh; Johanna Sjöstedt; Anders F. Andersson; Federico Baltar; Luisa W. Hugerth; Daniel Lundin; Saraladevi Muthusamy; Catherine Legrand; Jarone Pinhassi (Environmental Microbiology, 2015)
Summary Multiyear comparisons of bacterioplankton succession reveal that environmental conditions drive community shifts with repeatable patterns between years. However, corresponding insight into bacterioplankton dynamics at a temporal resolution relevant for detailed examination of variation and characteristics of specific populations within years is essentially lacking. During 1 year, we collected 46 samples in the B altic S ea for assessing bacterial community composition by 16S rRNA gene pyrosequencing (nearly twice weekly during productive season). Beta‐diversity analysis showed distinct clustering of samples, attributable to seemingly synchronous temporal transitions among populations (populations defined by 97% 16S rRNA gene sequence identity). A wide spectrum of bacterioplankton dynamics was evident, where divergent temporal patterns resulted both from pronounced differences in relative abundance and presence/absence of populations. Rates of change in relative abundance calculated for individual populations ranged from 0.23 to 1.79 day −1 . Populations that were persistently dominant, transiently abundant or generally rare were found in several major bacterial groups, implying evolution has favoured a similar variety of life strategies within these groups. These findings suggest that high temporal resolution sampling allows constraining the timescales and frequencies at which distinct populations transition between being abundant or rare, thus potentially providing clues about physical, chemical or biological forcing on bacterioplankton community structure.

O-methyltransferase(s)-suppressed plants produce lower amounts of phenolic vir inducers and are less susceptible to Agrobacterium tumefaciens infection - Stéphane Maury; A. Delaunay; F. Mesnard; D. Crônier; B. Chabbert; P. Geoffroy; M. Legrand (Planta, 2010)

Discussion of “Carboniferous stratigraphy and depositional environments in the Ahnet Mouydir area (Algerian Sahara)” by Wendt et al. (Facies 55(3):443–472, DOI 10.1007/s10347-008-0176-y) - Marie Legrand-Blain; Markus Aretz; Khireddine F. T. Atif (Facies, 2010)

Effect of prior heavy exercise on muscle deoxygenation kinetics at the onset of subsequent heavy exercise - A. Marles; S. Perrey; R. Legrand; N. Blondel; A. Delangles; D. Betbeder; P. Mucci; F. Prieur (European Journal of Applied Physiology, 2007)

Effect of high-intensity interval training and detraining on extra $${\dot{V}\hbox{O}_{2}}$$ and on the $${\dot{V}\hbox{O}_{2}}$$ slow component - A. Marles; R. Legrand; N. Blondel; P. Mucci; D. Betbeder; F. Prieur (European Journal of Applied Physiology, 2007)

Pinoresinol–lariciresinol reductase gene expression and secoisolariciresinol diglucoside accumulation in developing flax (Linum usitatissimum) seeds - C. Hano; I. Martin; O. Fliniaux; B. Legrand; L. Gutierrez; R. R. J. Arroo; F. Mesnard; F. Lamblin; E. Lainé (Planta, 2006)

The European Gravity Field and Steady-State Ocean Circulation Explorer Satellite Mission Its Impact on Geophysics - J. A. Johannessen; G. Balmino; C. Le Provost; R. Rummel; R. Sabadini; H. Sünkel; C.C. Tscherning; P. Visser; P. Woodworth; C. Hughes; P. Legrand; N. Sneeuw; et al. (Surveys in Geophysics, 2003)

Multicenter Evaluation of an Automated System Using Selected Bacteria That Harbor Challenging and Clinically Relevant Mechanisms of Resistance to Antibiotics - R. Leclercq; M.- Nicolas-Chanoine; P. Nordmann; A. Philippon; P. Marchais; A. Buu-Hoï; H. Chardon; H. Dabernat; F. Doucet-Populaire; C. Grasmick; P. Legrand; C. Muller-Serieys; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Subcellular localization of acidic and basic PR proteins in tobacco mosaic virus-infected tobacco - Isabelle Dore; M. Legrand; B. J. C. Cornelissen; J. F. Bol (Archives of Virology, 1991)